Numerical study of mixed convection and buoyancy ratio on MHD fluid flow beyond an inclined sheet - M. Azmi, H.; Parvin, S.; M. Isa, S. S. P.; M. Arifin, N.; H., Rosali (Institute of Physics, University of Latvia, 2021)
Mixed convection is commonly used in electronic cooling processes and nuclear reactor technology. As a result, this study aims to demonstrate the mathematical formulation of fluid flow, heat and mass transfer under the controlling physical parameters such as mixed convection, buoyancy ratio, suction, magnetic field, and rotation angle of the sheet. The variation in the wall shrinking velocity, temperature and concentration is expressed as an exponential function. Since controlling equations are partial differential equations, similarity transformations convert these partial differential equations to ordinary differential equations. Finally, these ordinary differential equations are considered as a non-linear and non-dimensional boundary value problem. The final solution of these ordinary differential equations is obtained numerically by applying the Matlab bvp4c programme. Stability analysis which determines the most stable numerical solution between duel solutions is also made using the Matlab bvp4c programme. Comparing the obtained computational results to previously published data shows a good agreement. All numerical results are graphically illustrated and explained, including the velocity, temperature and concentration profiles, skin friction coefficient, local Nusselt number, and local Sherwood number. Tables 2, Figs 7, Refs 41.